Visual FoxPro programming basics - Stearns, Tom.; Stearns, Leonard (Berkeley, Calif. : Osborne McGraw-Hill, 1996)
This text shows novice FoxPro users how to develop applications using all of FoxPro's programming tools. It focuses on giving the reader alternative methods of accomplishing tasks. For experienced users, there are tips and code examples to increase a database's speed, prouctivity and efficiency. The accompanying disk contains all the programming code in the book and is compatible with IBM PCs and databases.
Includes index.
oif 16/02/15
Loan
Keywords: Visual FoxPro for Windows; Application software -- Development; Database management